Procopius' Recalcitrant Reader (Wars 1.1.6–17) - Pazdernik, Charles F. (Histos)

(untitled) (University of Alberta Library, 2026)
A programmatic passage in the preface of Procopius of Caesarea’s Wars (1.1.6–17) focuses on how the work will be received by its implied audience. Procopius’ narrator posits two contrasting figures: one, an open-minded reader disposed to reason from historical evidence and to recognise the extraordinary qualities of contemporary events; the other, a recalcitrant reader whose valorisation of the past and immersion in linguistic archaism render him incapable of appreciating the present. The polemic against the latter is not a mere caricature, but a pretext for airing and displacing scepticism about the Wars’ axiological aims—that is, about what is most worth narrating and why it matters—especially with regard to the classical tradition in which the work participates.